1976
DOI: 10.1073/pnas.73.6.2113
|View full text |Cite
|
Sign up to set email alerts
|

Primate type-C virus nucleic acid sequences (woolly monkey and baboon types) in tissues from a patient with acute myelogenous leukemia and in viruses isolated from cultured cells of the same patient.

Abstract: Cultured peripheral blood leukocytes from a woman (patient HL23) with acute myelogenous leukemia produced type-C RNA tumor viruses (HL23V). The viruses were analyzed by molecular hybridization experiments after transmission to five secondary cell culture lines. Using the criteria of molecular hybridization, we concluded that al of the transmitted virus isolates have nucleotide sequences related to the genome of simian sarcoma virus (SiSV). In addition, in agreement with data reported elsewhere, some of the tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
14
0

Year Published

1977
1977
1983
1983

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(16 citation statements)
references
References 34 publications
1
14
0
Order By: Relevance
“…Several isolations have been made, one of which was from cultured myeloid leukaemia cells. This virus was closely related to simian sarcoma virus and baboon endogenous virus (Reitz et al, 1976), and it can be established as a chronic infection in various cell lines (Teich et al, 1975).…”
mentioning
confidence: 99%
“…Several isolations have been made, one of which was from cultured myeloid leukaemia cells. This virus was closely related to simian sarcoma virus and baboon endogenous virus (Reitz et al, 1976), and it can be established as a chronic infection in various cell lines (Teich et al, 1975).…”
mentioning
confidence: 99%
“…How ever, normal tissue DNA did contain sequences distantly related to baboon endogenous virus [11]. These work ers reportedly failed to detect an appreciable amount of sequences related to simian sarcoma virus in DNA from normal or neoplastic tissues [7,11,12]. The HL23 virus contained sequences indistinguishable from baboon endogenous virus as well as simian sarcoma virus [13], Paradoxically, simian-sarcoma-virus-related sequences were not detected even in DNA from the tissues of the patient from whose leukocytes HL23 virus was originally isolated [3,11].…”
Section: Introductionmentioning
confidence: 84%
“…Using complementary DNA (cDNA) prepared from oncornavirus-like cyto plasmic particles from human leukemic cells, Baxt and Spiegelman [10] reported that DNA from human leukemic cells contains particle-related sequences that were absent in DNA from leukocytes of normal individ uals. More recently, Reitz et al [7] and Wong-Staal et al [11] have detected in DNA from some human hematopoietic neoplastic tissues sequences related to baboon endogenous virus, murine leukemia virus 1 This work was supported in part by United States Public Health Service grant CA-15502 from the National Cancer Institute.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Virus isolates claimed to be candidate human type C viruses have been described which are related t o infectious primate type C virus (29)(30)(31) or to both infectious and endogenous primate type C viruses (32). T h e expression of p30 protein antigen related to baboon endogenous virus has been reported for normal tissues of the baboon and for some neoplastic tissues of the baboon a n d man ( I 1,13).…”
Section: Discussionmentioning
confidence: 99%